Darwin's super-pooping worm spectacular - Owen, Polly (Children's author) (Wide Eyed Editions, 2023)
The silly true story of how Darwin discovered that the earthworm is one of the most important species on the planet. Without their life-sustaining poop, there would be no plants or animals on Earth. A scholarly worm gives historical facts and context on every page.